Efficacy of ARB/HCTZ Combination Therapy in Uncontrolled Hypertensive Patients Compared with ARB Monotherapy: A Meta-Analysis. (27th April 2021) - Ma, Linlin; Zheng, Keyang; Yan, Jiafu; Cheng, Wenli
Abstract : Objective . To evaluate the efficacy of combination of angiotensin receptor blocker (ARB) with hydrochlorothiazide (HCTZ) compared to ARB alone in patients with uncontrolled hypertension via a systematic review and meta-analysis. Methods . We searched databases till July 2019 using relevant search terms. We included articles that were randomised controlled trials (RCTs) comparing ARB/HCTZ with ARB for a duration of at least 4 weeks and reported on the efficacy or safety. Meta-analyses for efficacy outcomes were performed. In addition, groups given different concentrations of HCTZ (12.5 and 25 mg) were analysed separately. Results . Sixteen RCTs (12, 055 participants) were included. Overall, ARB/HCTZ combination therapy (both 12.5 and 25 mg HCTZ combination) resulted in better sitting systolic and diastolic blood pressure control than ARB alone (mean difference (95% confidence interval (CI): −5.69 [−6.66, −4.73] for 12.5 mg and −9.10 [−11.78, −6.42] for 25 mg and mean difference (95% CI): −2.91 [−3.31, −2.51] for 12.5 mg and −4.16 [−4.75, −3.58] for 25 mg). ARB/HCTZ combination therapy resulted in a higher rate of target blood pressure achievement compared to ARB alone (risk ratio (95% CI): 1.50 [1.42, 1.59]). ARB/HCTZ combination therapy had similar rates of total adverse events (AEs) and severe AEs compared to ARB alone. Conclusion . ARB/HCTZ combination therapy is more efficacious for controlling blood pressure, and combination with a low concentration of HCTZ has similar AEs compared to ARB alone. Clinicians should consider adding HCTZ in the medication regime of patients with uncontrolled hypertension using ARB, if their clinical profile allows.